Seismic modeling of earthquake source Quindío (Colombia) from 25 january 1999 using waveform inversion teleseismic body (Revista de Investigaciones Universidad del Quindío, 2012)
In January 25th, 1999 Armenia earthquake (Mw = 6.2), up to now the largest shallow earthquake recorded instrumentally in the Colombian Eje Cafetero. It was located near Cordoba (Quindío) town, 17 kilometers from the Armenia (Colombia). The area and rupture process was obtained by inversion of teleseismic body waves, with broad band displacement records with wave ranges from 5 to 0.01 Hz. This process allowed to obtain a rupture area of 125 km2, a magnitude Mw = 6.0 and a left lateral strike – slip fault of unidirectional type. Since the presence of aftershocks indicate a that the fault rupture grew over time to the northeast, sug-gesting a fault of this type. The prevalent focal mechanism is strike – slip with a dip δ = 48.9°, an azimuth ϕ = 111.5° and a slip angle λ = -166.7° as a result of two subevents distributed along the rupture area; the first one occurred in τ =8 s y l=0 km and the second one located at τ =26 s y l=5 km. A hypocenter depth about 20 km was obtained, a seismic moment of 1.26 x 1025 dina*cm and a dislocation 0.324 m.The validation was made with acelerographics records of Red Sismológica Nacional de Colombia (RSNC) in two stations, the first one a far- field (at 141 km of distance to the earthquake) and the second one a near- field station (at 42 km of distance to the earthquake). With synthetic records of ground motion, was obtained an acceptable fit between the model and the recorded data.
Keywords: Armenia – Quindío (Colombia) earthquake; inversion of teleseismic body waves; focal mechanism; validation